ANALISIS FAKTOR KINERJA PEGAWAI - Prahyta Wiratamy; Beta Asteria (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2021)
Abstract This study aims to determine the effect of job training, work environment, and work motivation on employee performance in the BKAD Bantul Regency BPHTB Collection. The population in this study were all employees at the BKAD Bantul District BPHTB Billing Division. Samples taken by all employees of the BPHTB Billing Division were 52 respondents using the census method. The data analysis technique used in this study consisted of validity and reliability tests, classical assumption tests, multiple linear regression tests, hypothesis testing consisting of the F test and t test, and the coefficient of determination (R2) test. The results of this study indicate that: 1.) There is no positive effect of job training on employee performance. 2.) There is no positive influence of the work environment on employee performance. 3.) There is a positive effect of work motivation on employee performance.